Analisis Pengelolaan Keuangan Untuk Melihat Kinerja Sekolah Menegah Kejuruan Di SMK Negeri 1 Sukasada - Ni Nyoman Juli Nuryani (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
The purpose of this study was to analyze the planning and realization of the budget in the management of school finances at SMK Negeri 1 Sukasada. Direct costs and direct routine costs at SMK Negeri 1 Sukasada in 2017 to 2020 where the average tuition fee for students in the last 4 years has increased and decreased, in 2017 the average student tuition fee per month was Rp. 167.094, in 2018 the average monthly tuition fee for students is Rp. 193,666, where there was an increase in the average tuition fee of students in 2018 of Rp. 26,572, while in 2019 the average monthly tuition fee for students is Rp. 175,551, and in 2020 the average monthly tuition fee of students again increased by Rp. 182,375. Realization and budget at SMK Negeri 1 Sukasada in 2017 to 2020 where the budget ratio in the last 4 years has increased and decreased, in 2017 and 2018 the budget ratio was 0.99, where there was an increase in the budget ratio in 2019 of 0.01 to 1.00, while in 2020 the budget ratio again decreased by 0.07. When viewed from the ratio of income to expenditure at SMK Negeri 1 Sukasada in 2017 to 2020 where the ratio of income to expenditure in the last 4 years has increased and decreased, in 2017 and 2018 the budget ratio was 1.01, where there was a decrease in the ratio of income to expenditure in 2019 by 0.01 to 1.00, while in 2020 the expenditure income ratio again increased by 0.08.